In vivo Imaging of Mitochondrial Transport in Single-Axon Regeneration of Zebrafish Mauthner Cells - Xu, Yang; Chen, Min; Hu, Bingbing; Huang, Rongchen; Hu, Bing (Frontiers in Cellular Neuroscience, 2017)
Mitochondrial transport is essential for neuronal function, whereas the evidence of connections between mitochondrial transport and axonal regeneration in living vertebrate central nervous systems (CNS) remains limited. Here, we developed a novel model which can explore mitochondrial transport in a single Mauthner axon (M axons) of zebrafish by non-invasive in vivo imaging. To ensure the feasibility of this model, we treated labeled zebrafish with nocodazole and demonstrated that nocodazole could disrupt mitochondrial transport in this model. Meanwhile combining with two-photon laser axotomy, we precisely axotomized M axons and recorded M axonal regeneration and their mitochondrial transport in living zebrafish larvae simultaneously. The data proved that the injured axons which have a stronger regenerative capability accompanied with higher mitochondrial motility. Furthermore, in order to stimulate axonal regeneration, treating with dibutyryl cyclic adenosine monophosphate (db-cAMP) could also augment mitochondrial motility. Taken together, our results provided new insights that mitochondrial motility is positively correlated to axonal regeneration in living vertebrate CNS and this promising model we developed will be useful for further studies on the interaction of axonal regeneration with its mitochondrial dynamics through various genetic and pharmacological regulation.